PENERAPAN URBAN FARMING BERBASIS CIRCULAR ECONOMY DENGAN PEMANFAATAN LIMBAH RUMAH TANGGA - Suhaeni, Suhaeni; Wicaksana, Indrajit; Rahayu, Yayu Sri; Supriadi, Devie Rienzani; Khamid, Miftakhul Bakhrir Rozaq; Rianti, Winda (Universitas Padjadjaran, 2026)
Karawang Regency has undergone a significant transformation from an agrarian area into an industrial center, resulting in a reduction of agricultural land. This condition highlights the need for environmentally friendly urban agriculture practices, one of which is the implementation of urban farming based on a circular economy approach. This community service program was carried out in August 2025 in Sukaluyu Village, Karawang Regency, in collaboration with a women’s household group as the main partner. The program aimed to improve the skills and awareness of the community, particularly women, in processing household waste into compost fertilizer to support urban farming practices. The implementation methods included compost-making training, hands-on practice assistance, and evaluation through pre-tests and post-tests. The results showed a significant improvement in the participants’ understanding of the circular economy concept, the benefits of urban farming, and composting techniques, as reflected in the increase in evaluation scores from 60–72% in the pre-test to 83–87% in the post-test. In addition, participants were able to independently practice compost production using household waste, providing an alternative source of organic fertilizer that can be utilized in urban farming activities. In conclusion, the implementation of urban farming based on the circular economy proved effective in enhancing community capacity and encouraging more sustainable household environmental managementKabupaten Karawang mengalami perubahan signifikan dari daerah agraris menjadi pusat industri yang berdampak pada berkurangnya lahan pertanian. Kondisi tersebut mendorong perlunya inovasi pertanian perkotaan yang ramah lingkungan, salah satunya melalui penerapan urban farming berbasis circular economy. Kegiatan pengabdian kepada masyarakat ini dilaksanakan pada bulan Agustus 2025 di Kelurahan Sukaluyu, Kabupaten Karawang, dengan mitra utama kelompok ibu-ibu rumah tangga. Program ini bertujuan meningkatkan keterampilan dan kesadaran masyarakat, khususnya kelompok ibu-ibu di Kelurahan Sukaluyu, dalam mengolah limbah rumah tangga menjadi pupuk kompos untuk mendukung praktik urban farming. Metode pelaksanaan mencakup pelatihan pembuatan kompos, pendampingan praktik, serta evaluasi melalui pre-test dan post-test. Hasil kegiatan menunjukkan adanya peningkatan signifikan pemahaman peserta mengenai konsep circular economy, manfaat urban farming, dan teknik pembuatan kompos, yang ditunjukkan oleh kenaikan skor evaluasi dari 60–72% pada pre-test menjadi 83–87% pada post-test. Selain itu, peserta mampu mempraktikkan pembuatan kompos secara mandiri dengan memanfaatkan limbah rumah tangga, sehingga memiliki alternatif sumber pupuk organik yang dapat digunakan dalam kegiatan urban farming. Kesimpulan dari kegiatan ini adalah penerapan urban farming berbasis circular economy terbukti efektif dalam meningkatkan kapasitas masyarakat dan mendorong perilaku pengelolaan lingkungan yang lebih berkelanjutan.